Comment on: Global variation in anastomosis and end colostomy formation following left-sided colorectal resection. Issue 3 (22nd May 2021) - Schaps, D; Alvarez, C E
Abstract : Is the corresponding author a member of a Strategic Partner Society (50% discount on article publication charge):